2017
DOI: 10.1001/jamadermatol.2016.4604
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Outcomes for Cutaneous Head and Neck Melanoma

Abstract: In this issue, Moyer and colleagues 1 report long-term follow-up of a large cohort of patients with head and neck melanoma treated with a "square" staged excision technique using permanent sections for comprehensive margin assessment. The median follow-up of 9.3 years demonstrated excellent long-term disease control of 834 lesions with projected local recurrence rate of 2.2% at 10 years. The mean margin required for histologic clearance of tumor was 9.3 mm for melanoma in situ and 13.7 mm for invasive melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Although dermoscopy and Wood lamp examination have been used to guide LM excisions, in our study in approximately 40% of the quadrants, HRCM identified LM and/or LMM extending beyond the dermoscopic and Wood lamp margins. These results highlight that HRCM improves LM and LMM margin evaluation and confirm the need for increased surgical margins to achieve clear margins . We used an imaging approach that parallels the design of staged excision with radial histopathologic sectioning by imaging with HRCM radially from the center to the periphery.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although dermoscopy and Wood lamp examination have been used to guide LM excisions, in our study in approximately 40% of the quadrants, HRCM identified LM and/or LMM extending beyond the dermoscopic and Wood lamp margins. These results highlight that HRCM improves LM and LMM margin evaluation and confirm the need for increased surgical margins to achieve clear margins . We used an imaging approach that parallels the design of staged excision with radial histopathologic sectioning by imaging with HRCM radially from the center to the periphery.…”
Section: Discussionmentioning
confidence: 69%
“…These results highlight that HRCM improves LM and LMM margin evaluation 12,14,15 and confirm the need for increased surgical margins to achieve clear margins. 4,[24][25][26] We used an imaging approach that parallels the design of staged excision with radial histopathologic sectioning by imaging with HRCM radially from the center to the periphery. Our results suggest that HRCM-RV correlates with surgical defects after staged excision of LM and LMM, although the mean HRCM-RV estimates were smaller than the actual defect.…”
Section: Discussionmentioning
confidence: 99%